PARTICIPATION OF PEOPLE ON PERFORMANCE OF DEVELOPING PLAN FOR AGRICULTURE IN KHONG CHIAM SUB-DISTRICT OF KHONG CHIAM DISTRICT IN UBONRATCHATHANI PROVINCE - Somsa, Supan (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research were I, to study the level on participation of people for performance of developing plan on agriculture in Khong Chiam Sub district, 2, to compare the participation of people on performance of developing plan for agriculture in Khong Chiam Sub-district and 3, to study the guidelines on participation of people for performance of developing plan on ahriculture in Khong Chiam Sub-district of Khong Chiam District in Ubonratchathani Province. The samples using in this research were 335 persons from the chiefs of families in Khong Chiam Sub-district and the purposive groups were 40 persons by using questionnaires and semi-structured interviews The statistics using for data analyzing included frequency, percentage, percentage, mean and standard deviation the hypothesis testing using t-test (Independent Sample) and F-test (One Way ANOVA). The results of findings were as follows; 1. For overall on participation of people for performance of developing plan on agriculture in Khong Chiam Sub-district of Khong Chiam District in Ubonratchathani Province was in medium level. 2. The Result of comparative analysis on participation of people for performance of developing plan in Khong Chiam Sub-District of Khong Chiam District in Ubonratchathani Province. The chiefs of families in Khong Chiam Sub-District of Khong Chiam District in Ubonratchathani Province with different gender, age, educational level and occupation were participated on Khong Chiam Sub-District of Khong Chiam District in Ubonratchathani Province and were statistically significant different at .05 level. 3. Guidelines for public participation in the preparation of the Khong Chiam Subdistrict Agricultural Development Plan. Khong Chiam District Ubon Ratchathani Province Overall, it is at a moderate level. When considering each aspect, the aspect with the highest average was problem presentation, followed by action planning. Operational aspect and benefits, respectively, while the side with the lowest average was the follow-up and evaluation aspect.